Cell Formation Heuristic Procedure Considering Production Data - Shailendra Kumar; Rajiv Kumar Sharma (International Journal of Production Management and Engineering)
Manufacturing cell formation is one of foremost, and critical aspect of any manufacturing cell design problem. A large number of cell formation methods are developed and still counting. Consideration of production data in cell formation makes these methods more complex and tedious. In this paper an attempt has been made to develop a simple, easy to understand and implement cell formation procedure, having the capability to handle production data viz. operation sequence, production volume, and inter-cell movement cost simultaneously. The results obtained from proposed procedures are in tune with some highly complex methods, which validates the performance of proposed procedure. To demonstrate its ability to handle other production parameters with little modifications, a modification for consideration to part processing cost in addition to above mentioned production data is developed and explained. Towards the end the procedure to handle alternate process plans in conjugation with production data by the proposed cell formation procedure is also discussed.